LIBRARIAN INTERPERSONAL COMMUNICATION IN IMPROVING SERVICE QUALITY AT THE SYEKH YUSUF LIBRARY UIN ALAUDDIN MAKASSAR - Jabbar, Fitriani; Iskandar, Iskandar; Yaumi, Muhammad; Ahmad, La Ode Ismail; Ibrahim, Andi (Jurnal Diskursus Islam, 2021)
This study aims to describe the interpersonal communication skills of librarians in building good relationships with users. The type of research used is qualitative with a descriptive approach. The method used is a methodological and scientific approach. The data is obtained using interview, observation and documentation guidelines. The data analysis is using data reduction, data display, and verification. The results showed that basically, the interpersonal communication of librarians in serving the users was quite good. However, the attitude of respect, empathy, audible, celebratory and humble shown by the Librarian towards the users is still less prominent and does not have clear standards. Thus librarians become less proactive in serving users.